Does Simulator Sickness Impair Learning Decision Making While Driving a Police Vehicle? | Le mal du simulateur: un frein à l’apprentissage de la prise de décision en conduite d’un véhicule de police? - Paquette, Eve; Bélanger, Danielle-Claude (Canadian Journal of Learning and Technology, 2015)
The use of driving simulators is an innovation for police training in Quebec. There are some issues related to their impact on training objectives. This article presents the results of a study involving 71 police cadets who participated in six training sessions with a driving simulator. The training sessions were designed to competencies development to make decisions during emergency driving and pursuit. The nature and consequences of the discomfort experienced by the participants is described. The results highlight the importance of the initial training session. Issues related to providing trainees with adequate support are discussed.Le simulateur de conduite est un outil pédagogique novateur pour la formation policière au Québec. Il comporte des enjeux à l’égard de l’atteinte des objectifs pédagogiques visés. L’article présente les résultats d’une recherche menée auprès de 71 aspirants policiers ayant participé à une formation de six séances au simulateur de conduite visant le développement des compétences en matière de prise de décision en conduite d’urgence et en poursuite. Les résultats dressent un portrait des malaises ressentis par les participants et de leurs impacts. Les résultats montrent également l’importance de la première séance. La discussion s’attarde aux enjeux liés à l’accompagnement des apprenants.